2012
DOI: 10.4103/1658-354x.93046
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of propofol versus sevoflurane on thermoregulation in patients undergoing transsphenoidal pituitary surgery: A preliminary study

Abstract: Purpose:General anesthesia causes inhibition of thermoregulatory mechanisms. Propofol has been reported to cause more temperature fall, but in case of deliberate mild hypothermia, both sevoflurane and propofol were comparable. Thermoregulation is found to be disturbed in cases of pituitary tumors. We aimed to investigate which of the two agents, sevoflurane or propofol, results in better preservation of thermoregulation in patients undergoing transsphenoidal excision of pituitary tumors.Methods:Twenty-six pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 10 publications
(14 reference statements)
0
6
1
Order By: Relevance
“…Sixth, we did not compare clinically important outcomes, such as intraoperative hemodynamics and recovery profiles from anesthesia, between sevoflurane and propofol groups. However, previous studies showed no clinically significant differences in terms of perioperative hemodynamics, intraoperative thermoregulation and blood loss, time to extubation, length of stay in the post‐anesthesia recovery room, and operating conditions between sevoflurane and propofol anesthesia for ETS 23‐27 . Lastly, the non‐inferiority margin was as high as 9% in this study.…”
Section: Discussioncontrasting
confidence: 62%
“…Sixth, we did not compare clinically important outcomes, such as intraoperative hemodynamics and recovery profiles from anesthesia, between sevoflurane and propofol groups. However, previous studies showed no clinically significant differences in terms of perioperative hemodynamics, intraoperative thermoregulation and blood loss, time to extubation, length of stay in the post‐anesthesia recovery room, and operating conditions between sevoflurane and propofol anesthesia for ETS 23‐27 . Lastly, the non‐inferiority margin was as high as 9% in this study.…”
Section: Discussioncontrasting
confidence: 62%
“…34 Other studies found no difference in wake-up between sevoflurane and propofol, but did not assess 35 or found no difference in blood loss between the groups. 18 There was also no difference in the severity of stress response during pituitary surgery between TIVA and sevoflurane/N 2 O inhaled anesthesia. 36 Consequently, pertinent review articles on perioperative management of patients undergoing endoscopic transsphenoidal surgery do not recommend one particular anesthetic technique over another, 14 as long as a reasonably rapid recovery for timely postoperative neurological assessment is facilitated 3,4 for which shorter acting volatile anesthetics or propofol appear to have an advantage over isoflurane.…”
Section: Discussionmentioning
confidence: 89%
“…A power analysis based on Chowdhury et al 18 revealed a sample size of 45 patients per group to find a clinically relevant decrease in EBL of 25% with a power of 80%. After approval by the Institutional Review Board of the Medical College of Wisconsin (MCW), we conducted a retrospective chart analysis of 193 American Society of Anesthesiologists (ASA) class 1 to 3 patients who had undergone transsphenoidal, endonasal resections of pituitary tumors at MCW over a seven-year time period.…”
Section: Methodsmentioning
confidence: 99%
“…The investigations performed by Kwak et al support this decision in that body temperature did not differ when using the two types of anesthesia mentioned above [12]. Although Propofol has been reported to cause a lower body temperature in comparison to narcotic gases they were comparable in conditions of mild perioperative hypothermia [13].…”
Section: Methodsmentioning
confidence: 90%